Chronic Pain Patients’ Perspectives of Medical Cannabis - Piper, Brian J (Pain, 2017)
Medical cannabis patients, including two-thirds with chronic-pain, report health benefits including improved pain management and sleep. Pharmacoeconomic factors were the greatest limitation of medical cannabis.